Effect of Fe3O4 Nanoparticle and Graphene Oxide Compositions on The Magnetic Properties of Fe3O4 : Graphene Oxide Nanocomposites - Ramadhani, Dinda; Hidayat, Rahmat; Ratnawulan, Ratnawulan; Darvina, Yenni (Journal of Experimental and Applied Physics, 2024)
Magnetic material research aims to determine the effect of variations in the addition of Fe3O4 nanoparticles to graphene oxide. Graphene oxide made from coconut shell waste was synthesized using the modified hummers method and composited with Fe3O4 nanoparticles consisting of three composition variations, which are 20%:80%, 30%:70% and 40%:60%. The Fe3O4-Graphene Oxide nanocomposite was tested using three characterization tools, namely XRD, FTIR and VSM. Testing using XRD and FTIR was carried out to determine whether the Fe3O4-Graphene Oxide nanocomposite had been formed or not. In XRD testing, a crystal size of 39.57 nm was obtained, which means that this research has succeeded in forming nanocomposites where the size obtained is smaller than 100 nm. In FTIR testing, it can also be seen that this research has succeeded in forming Fe3O4-Graphene Oxide nanocomposites as seen from the functional groups obtained, which consist of oxygen, hydrogen, carbon and iron. In testing using VSM, it can be seen how the effect of adding Fe3O4 to graphene oxide, where the greater the addition of Fe3O4 composition, the greater the value of the coercivity field produced. In addition, the addition of Fe3O4 causes an increase in the magnetic properties of remanent magnetic, saturation magnetic  and coercivity values. The coercivity values are 371.18 Oe, 387.59 Oe and 405.19 Oe, respectively, where the highest coercivity value is found in the 40% variation: 60%. This hail shows that the nanocomposite produced is ferromagnetic and classified as a hard magnet so that it can be applied as HDD.